Frequency of Neonatal Morbidity and Mortality in Intrauterine Growth-Restricted Term Pregnancies in Karachi: A Hospital-Based Cross-Sectional Study: Neonatal Morbidity and Mortality in Intrauterine Growth-Restricted Term Pregnancies - Aslam, Yusra; Naqvi, Zehra; Khan, Yumna Qamar (Pakistan Journal of Health Sciences, 2026)
Intrauterine growth restriction (IUGR) is a major cause of illness and death in neonates. Growth-restricted term neonates are susceptible to hypoglycemia, respiratory distress, and perinatal mortality. Objective: To determine the frequency of neonatal morbidity and mortality among intrauterine growth-restricted (IUGR) term pregnancies. Methods: A hospital-based cross-sectional study was performed at the Department of Obstetrics and Gynecology, Liaquat National Hospital, Karachi, from June to November 2024. A total of 143 women with singleton term pregnancies (≥ 37 weeks diagnosed with intrauterine growth restriction (IUGR) due to estimated fetal weight below the 10th percentile were enrolled through consecutive sampling. Neonatal outcomes were documented. Categorical variables were presented as frequency and percentage. A p-value of ≤ 0.005 was deemed statistically significant. Results: The median maternal age was 29 years, with a 30.8% having a history of IUGR and 37.8% experiencing intrauterine death; 53.1% delivered vaginally and 46.9% through a cesarean section. Meconium aspiration occurred on 31.5%, low birth weight in 9.1%, and NICU admission in 35.0%, with hypoglycemia (2.1%) and perinatal mortality (4.9%) being uncommon. Lower maternal age was associated with low birth weight and hypoglycemia, adverse Apgar scores with adverse neonatal outcomes, and increased NICU admission after cesarean delivery. Conclusions: Intrauterine growth-restricted term pregnancies are strongly associated with adverse perinatal outcomes, including respiratory compromise, metabolic instability, and increased risk of mortality.